Stress Management In Traders During Covid-19 Pandemic In Ringinrejo Hamlet Kebonsari Village Kademangan District Blitar Regency - Gita, Visia Luh; Humairo, Mika Vernicia (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2020)
Everything changed drastically when covid-19 invaded the world. Starting from the economic order, state policies, from the largest to the smallest structures, are no exception with traders. The changes that occur both large and small, make it difficult for many people to re-adjust. If pulled in more depth, there will be emotional instability, the appearance of various anxiety disorders, to stress. The purpose of this study is to find out the stress management of traders during the covid-19 pandemic in Ringinrejo Hamlet Kebonsari Village Kademangan district Blitar Regency. The research method used in this study is qualitative method. This study uses Snawball Sampling technique. The population in this study was the people of Ringinrejo Hamlet Kebonsari Village Kademangan district Blitar Regency with a sample count of 7 Respondents and 7 source triangulation. The Data collection process was conducted with in-depth interviews, observations and documentation on traders in Ringinrejo Hamlet. Data analysis techniques through data collection stages, data reduction, data display and conclusion verification. Test the validity of data using source triangulation. The results showed that traders during this pandemic emerged symptoms of mild stress such as health and emotional problems. The main factors influencing the stress of traders in the pandemic are the difficulty of selling during the pandemic and the fear of contracting the virus from others. Various ways are done by traders to overcome stress so as not to cause severe stress until there is depression such as exercising, telling stories with family, staying positive, praying, gathering with the surrounding environment, watching soap operas, watching football, eating healthy foods so that the immune system does not go down and limits information related to covid-19. Stress can affect a person's physical, mental and emotional state. Therefore it is important for everyone to have knowledge and ability in managing stress. By understanding the theory and concept of stress, one can have full power in controlling oneself and his emotions so that he can optimize his abilities and strengths.